Practical approaches for the treatment of chronic heart failure: Frequently asked questions, overlooked points and controversial issues in current clinical practice - (:unkn) unknown (TURKISH SOC CARDIOLOGY, 2015)
Heart failure (HF) is a progressive disorder associated with impaired quality of life, high morbidity, mortality and frequent hospitalization and affects millions of people from all around the world. Despite further improvements in HF therapy, mortality and morbidity remains to be very high. The life-long treatment, frequent hospitalization, and sophisticated and very expensive device therapies for HF also leads a substantial economic burden on the health care system. Therefore, implementation of evidence-based guideline-recommended therapy is very important to overcome its worse clinical outcomes. However, HF therapy is a long process that has many drawbacks and sometimes HF guidelines cannot answers to every question which rises in everyday clinical practice. In this paper, commonly encountered questions, overlooked points, controversial issues, management strategies in grey zone and problems arising during follow up of a HF patient in real life clinical practice have been addressed in the form of expert opinions based on the available data in the literature.
Keywords: algorithm; drugs; heart failure; strategies; therapy; CONVERTING-ENZYME-INHIBITORS; PRESERVED EJECTION FRACTION; LEFT-VENTRICULAR DYSFUNCTION; CHRONIC KIDNEY-DISEASE; PULMONARY ARTERIAL-HYPERTENSION; ANGIOTENSIN-ALDOSTERONE SYSTEM; BETA-BLOCKER THERAPY; CARDIAC-INSUFFICIENCY BISOPROLOL; RANDOMIZED INTERVENTION TRIAL; POLYUNSATURATED FATTY-ACIDS